Molecular Engineering of Exchange Bias in Fe3GeTe2/Molecule Heterostructures - Şahin, Hasan; Sharma, Mayank; Jo, Junhyeon; Avedissian, Garen; Bayindir, Bertug; Kang, Jun; Sahin, Hasan; Hueso, Luis E. (Amer Chemical Soc, 2025)
Molecules offer a versatile route to tailor magnetism through chemical design and spin-state control. When integrated with surface-sensitive layered magnets, molecules can not only exhibit tunable magnetic properties or even activate distinct magnetic phases but can also interact with the layered magnets to manipulate their magnetic dynamics. Here, we demonstrate tunable exchange bias in hybrid heterostructures composed of the layered ferromagnet Fe3GeTe2 (FGT) and metallophthalocyanine (MPc) molecules having different central transition ions: MnPc, ZnPc, and H2Pc. The MnPc/FGT system exhibits a robust exchange bias of 1000 Oe at 10 K, with a record-high exchange bias-to-coercivity ratio of 0.37, attributed to the antiferromagnetic nature of MnPc. Surprisingly, the diamagnetic ZnPc induces a finite exchange bias of 200 Oe, highlighting the contribution of the emerging spinterface effect. In contrast, the metal-free H2Pc yields no exchange bias, underscoring the essential role of designed molecules for magnetic interaction. First-principles calculations reveal energetically favorable stacking configurations and spin alignments, in agreement with experimental observations. These results highlight the potential of molecular functionalization on magnetism, enabling the on-demand engineering of layered magnetic systems.
Hueso, Luis/0000-0002-7918-8047; Casanova, Felix/0000-0003-0316-2163
Keywords: 2D Magnets; Fe3Gete2; Exchange Bias; Spinterface; Metal Phthalocyanine